Hubungan petanda inflamasi dan hemoglobin pada obesitas di Fakultas Kedokteran Universitas Diponegoro periode Mei-September 2018 - Emelia Wijayanti; Dwi Retnoningrum; Meita Hendrianintyas (Intisari Sains Medis, 2019)
Introduction: Obesity is one of global epidemic health problems. Obesity has been suggested to be associated with a state of chronic low-grade inflammation, which is characterized by abnormal cytokine production, increased acutephase reactants and activation of inflammatory signaling pathways. NLR (neutrofil to lymphocyte ratio) a simple and reliable indicator of inflammation, have been reported to be associatied with metabolyc syndrom, insulin resitence, and obeity in more study. Ferritin is a marker of inflammation contribute in obesity, and have been reported that ferritin is a marker of inflammation rather than iron status in overweight and obese people. Relationship between anemia and obesity may be due to fat a ccumulation and chronic inflammation in adipose tissue can be decreased iron absorbtion.Methods: Cross-sectional study of 50 obesity subject, based on Riskesdas criteria, on Mei – September 2018. Marker of inflammation is ferritin serum was measured by ELISA (enzyme linked immunosorbent assay), and NLR and haemoglobin was perfomed from haematology analyzer. Spearman test was perfomed for analyzing data with p <0,05 was significantResults: No correlation between NLR and haemoglobin, r= 0,067 and p= 0,642, and significant strong positive correlation between ferritin and haemoglobin, r= 0,630 and p < 0,000.Conclusion: There was no correlation between NLR and haemoglobin, and there was significant strong positive correlation between ferritin and haemoglobin in obesity. Future research need to observe with evaluate hepcidin, other iron status parameter and marker of inflammation.